Judicialização da saúde na voz do usuário: a procura do cuidado através da justiça - Capiberibe, Cláudia Camargo [UNIFESP] (2019)
Introduction: In Brazil, health has been a constitutional right since 1988, but the lack of full service to the population by SUS [Sistema Única de Saúde – Brazil’s public healthcare system] or the private sector has led to the judicialization of health, a legal recourse that allows for the enforceability of rights when these are denied by the parties responsible, and which has transformed into an alternative means for accessing medicines, services and products not covered by the policies and protocols of SUS or on the lists of the ANS [Brazil’s National Health Agency]. It is a phenomenon that involves multiple parties, with distinct and often conflicting objectives and interests. Studies have shown that the judicialization of health is a legitimate form of pressuring the State, but one which has relevant secondary effects, such as significant impact on costs and increasing inequalities in access to and use of healthcare services. Its complexity and effects have been well studied, but the point of view of the user has been mostly ignored. Objective: To analyze the experiences of people who have sought redress in the courts to have access to services and to guarantee their health. Methodology: The investigation, based on a micropolitical approach, was conducted through qualitative research. Seven interviews were carried out with people who reside in Sao Paulo and have initiated court actions, selected at random from the search tool of the Sao Paulo Court of Justice and through indications from de first selected interviewed. Resorting to personal documents and using oral history techniques, the research seeks to identify the users' care maps, the obstacles they face, as well as the strategies and mechanisms used to attain their health objectives. Results and Discussion: The data from the research was organized along cutting-planes: the experience with the infirmity and the experience with the judicialization process. The first permitted the construction of care maps and the second allowed for the description and analysis of the trajectory relative to the legal requests. These experiences played out in different planes of visibility, with relevant meanings, made visible/utterable by repeated examination of the narratives. The users initiate actions in the Court against SUS and/or the private healthcare provider motivated fundamentally by their suffering and the desire to recover autonomy, reduce the financial impact of the infirmity and by the belief that therapies and innovative technologies not yet contemplated by the System might provide better quality of life. They see themselves as guaranteeing unseen and unconsidered health needs, exercising a kind of "social control" and demanding fair return for taxes paid. The Court becomes an important and decisive point on the care maps of these users and their families. Judicialization, however, ends up becoming yet another form of regulating access to use of the healthcare system and a form of privileged access to public funds, creating a “marketplace” for health services and products, a shortcut for technological incorporation and greater iniquity. To the users, however, the parties that act in this complex arena are not motivated by personal interests or economic gain. Instead, they are imagined to be links in the system willing to produce alternatives so that the care map may be complemented or improved, without any moral or ethical judgement, as well as providing an individualized solution. Conclusion: The empirical results of the research demonstrate that there is great diversity in the narrated experiences, which allowed for the identification of various facets to the judicialization of healthcare. The most common and relevant to the users who go through the experience is the desire to survive the infirmity, recover their health and improve their quality of life, whatever the cost and through whatever means at their disposal, including judicialization, and despite regulations or other rules of the system or societal interests, which appear to be insufficient to limit their actions.